2017
DOI: 10.1108/jstp-02-2016-0044
|View full text |Cite
|
Sign up to set email alerts
|

Service excellence in the light of cultural diversity: the impact of metacognitive cultural intelligence

Abstract: Purpose The purpose of this paper is to understand when, how, and why service employees adapt the service encounter to meet the values and expectations of culturally disparate customers. Design/methodology/approach The authors tested the hypothesized framework utilizing a scenario-based experimental study. In total, a sample of 296 prospective restaurant service employees were asked to evaluate their willingness to adapt their behavior when faced with cultural differences as well as out group status. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 73 publications
2
21
0
Order By: Relevance
“…Insert Table 5 about here CQ has been found to be an important moderator in various contexts, including expatriation (Froese, Kim, & Eng, 2016), business travel (Ramsey, Leonel, Gomes, & Monteiro, 2011), education (Jie & Harms, 2017), export (Magnusson, Westjohn, Semenov, Randrianasolo, & Zdravkovic, 2013), international study (Presbitero, 2016b;Volpone, Marquardt, Casper, & Avery, 2018), intercultural service encounters (Lorenz, Ramsey, Tariq, & Morrell, 2017), and intercultural teamwork (Rosenauer, Homan, Horstmeier, & Voelpel, 2016). In general, CQ strengthens the relationship between intercultural differences and cross-cultural adjustment and performance (Lorenz et al, 2017;Magnusson et al, 2013;Rosenauer et al, 2016) and diminishes the relationship between such differences and adaption problems as strain (Ramsey et al, 2011). For example, Rosenauer et al (2016) found that teams with higher national diversity have a better performance only when team leaders' CQ and task interdependence are high.…”
Section: Moderating Effects Of Cultural Intelligencementioning
confidence: 99%
“…Insert Table 5 about here CQ has been found to be an important moderator in various contexts, including expatriation (Froese, Kim, & Eng, 2016), business travel (Ramsey, Leonel, Gomes, & Monteiro, 2011), education (Jie & Harms, 2017), export (Magnusson, Westjohn, Semenov, Randrianasolo, & Zdravkovic, 2013), international study (Presbitero, 2016b;Volpone, Marquardt, Casper, & Avery, 2018), intercultural service encounters (Lorenz, Ramsey, Tariq, & Morrell, 2017), and intercultural teamwork (Rosenauer, Homan, Horstmeier, & Voelpel, 2016). In general, CQ strengthens the relationship between intercultural differences and cross-cultural adjustment and performance (Lorenz et al, 2017;Magnusson et al, 2013;Rosenauer et al, 2016) and diminishes the relationship between such differences and adaption problems as strain (Ramsey et al, 2011). For example, Rosenauer et al (2016) found that teams with higher national diversity have a better performance only when team leaders' CQ and task interdependence are high.…”
Section: Moderating Effects Of Cultural Intelligencementioning
confidence: 99%
“…Bogilovi c et al (2017) found that CQ attenuates the negative relationship between individual knowledge hiding and individual creativity. Furthermore, CQ positively moderated the relationship between perceived cultural differences and out-group status (Lorenz et al, 2017). Presbitero and Toledano (2018) H6.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 94%
“…In general, studies have shown that cultural intelligence has many cognitive, emotional and behavioral consequences (Yari and Lankut, 2020;Sharma, 2019;Presbitero, 2020). Also, cultural intelligence has been found to be an important moderator in various contexts, including expatriation (Froese et al, 2016), business travel (Ramsey et al, 2011), education (Jie and Harms, 2017), export (Magnusson et al, 2013), international study (Presbitero, 2016;Volpone et al, 2018), intercultural service encounters (Lorenz et al, 2017) and intercultural teamwork (Rosenauer et al, 2016). For example, Rosenauer et al (2016) found that teams with higher national diversity have a better performance only when team leaders' CQ and task interdependence are high.…”
Section: Moderating Role Of Cultural Intelligencementioning
confidence: 99%